Integrating youth into change mantra through renewal of wearing cloth (iwa akwa) rite among the Igbo people of Nigeria (2018)
Clothing rite, a major aspect of the culture that affects Nigerian in the new drive towards a better Nigeria via change mantra has not received much attention in the previous scholarly works on how to achieve the so much change in Nigeria. This is the gap this paper filled as it adopted interview, observation and focus grip discussion as research methods at tools to probe the ' wearing Cloth Religious Rites’ among the Igbo people of Nigeria. Consequently, it underscores the trust of the tradition which consists of some socio - religious activities such as dedication to duty, honesty in social relations, participation in community development and shunning all indecent behaviour often associated with youthful exuberance. Leaning on Durkheim theory of functionalism of religion, the paper proves that integration of the tradition as a home grown agent of change would help drive home the philosophy of Buhari’s change agenda. This is predicated on the fact that the youth are energetic, aware of the importance of socialization and building friendship using modern technologies and communication facilities to advance change and development